2010
DOI: 10.1016/j.wasman.2010.02.023
|View full text |Cite
|
Sign up to set email alerts
|

The use of life cycle assessment for the comparison of biowaste composting at home and full scale

Abstract: Environmental impacts and gaseous emissions associated to home and industrial composting of the source-separated organic fraction of municipal solid waste have been evaluated using the environmental tool of life cycle assessment (LCA). Experimental data of both scenarios were experimentally collected. The functional unit used was one ton of organic waste. Ammonia, methane and nitrous oxide released from home composting (HC) were more than five times higher than those of industrial composting (IC) but the latte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
83
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 170 publications
(99 citation statements)
references
References 24 publications
14
83
0
2
Order By: Relevance
“…including leftovers of raw fruits and vegetables, food scraps and raw fish or meat and other similar wastes) have also been studied and compared to full-scale plants. Complete details of this study can be found in Martínez-Blanco et al 25 HC was performed in a composting bin (70 ×70 ×103 cm) placed outdoors in the Escola d'Enginyeria of the Universitat Autònoma de Barcelona (Bellaterra, Spain).…”
Section: Treatment Facilities Studiedmentioning
confidence: 99%
See 2 more Smart Citations
“…including leftovers of raw fruits and vegetables, food scraps and raw fish or meat and other similar wastes) have also been studied and compared to full-scale plants. Complete details of this study can be found in Martínez-Blanco et al 25 HC was performed in a composting bin (70 ×70 ×103 cm) placed outdoors in the Escola d'Enginyeria of the Universitat Autònoma de Barcelona (Bellaterra, Spain).…”
Section: Treatment Facilities Studiedmentioning
confidence: 99%
“…A specific methodology was developed to calculate gaseous emissions from the composting process 25,28,29 and from biofilters 30 . In brief, airflow velocity and ammonia, nitrous oxide, methane and VOC concentrations on the surface of the composting pile, composting bin or the biofilter were simultaneously measured on the material surface of the composter in order to calculate the gas outlet emission rate (mg/s).…”
Section: Determination Of Input and Output Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…LCI data regarding material extraction, processing, transportation and electricity generation were obtained from the ecoinvent database 3.0 [70], while literature data were used for compost production [61] (background data). When background data was employed, the datasets were adapted to the geographical context of the case study of Padua (Italy), thereby indicating the consumption of Italian resources (e.g., natural gas, electricity, water) and of materials produced in their origin markets.…”
Section: Data Quality and Geographical Adaptationmentioning
confidence: 99%
“…Contudo, questões de escala são relevantes, como discutido por Martínez-Blanco et al (2010), mediante a análise do ciclo de vida, que evidencia as vantagens ambientais da compostagem em pequena escala em comparação à de escala industrial, pois, mesmo predominantemente aeróbica, a compostagem pode ser fonte de CH 4 , NH 3 , NO 3 , SO 2 e N 2 O.…”
Section: Introductionunclassified